Comparative exergy and economic assessment of fossil and biomass-based routes for ammonia production. (15th August 2019) - Flórez-Orrego, Daniel; Maréchal, François; de Oliveira Junior, Silvio
Highlights: The exergy efficiency of the natural gas and biomass-based ammonia production average 65.8% and 41.3%. The overall emission balances vary from 0.5 to −2.3 tCO2 /tNH3 for fossil and biomass-based routes, respectively. Higher operating revenues are achieved by fully replacing costly natural gas fuel and electricity imports. The feedstock supply chain irreversibility entails a 10–15% lower extended ammonia production efficiency. Abstract: The use of biomass gasification for partially or totally replacing methane in the integrated syngas and ammonia production plant is compared with the performance of the conventional route, typically based on steam methane reforming. However, by undertaking novel designs, additional or totally different demands are created. Consequently, the optimal integration approach between the new chemical plant and the alternative utility systems must be updated, so that the power and steam requirements remain satisfied. To this end, a systematic framework that allows selecting the most suitable utility systems whereas satisfying the minimum energy requirements (MER) with lower operating cost is adopted. The combined energy integration and exergy analyses proved to be relevant, especially regarding the integration of reactive components and the combined heat and power production (CHP) as well as the reduction of avoidable exergy losses. The exergy efficiencies of the natural gas and biomass-based ammonia production plants average 65.8% and 41.3%, respectively, and the overall emission balances vary from 0.5 to −2.3 tCO2 /tNH3, respectively. Despite the lower efficiency, higher operating revenues are achieved by totally replacing the costly natural gas input and avoiding the electricity import, favoring the consumption of a fraction of the syngas produced as fuel. Finally, it must be noticed that by defining an extended industrial framework, the inefficiencies at the upstream feedstock supply chains can be also accounted for, which entails a further reduction of 10–15% of the overall ammonia production efficiency. Accordingly, even by fully substituting the natural gas consumption with renewable energy resources, the sustainability of the overall system becomes rather an intricate function of the performance of the feedstock supply chains, the electricity mix enclosing the chemical system, the ammonia production plant and the main components thereof, as well as of the cost ratio of the resources consumed.